Evolution of microstructure and performance in magnesium potassium phosphate ceramics: Role of sintering temperature of MgO powder. Issue 14 (1st November 2016) - Viani, Alberto; Sotiriadis, Konstantinos; Šašek, Petr; Appavou, Marie-Sousai
Abstract: The reactivity of the MgO powder employed in the formulation of Mg–K phosphate ceramics can be modulated through the calcination temperature of MgCO3 source material, which has a direct impact on production costs. Upon annealing, MgO undergoes sintering, and in order to optimize the design of products for applications, it is of primary importance to disclose the link between the sintering temperature, reaction mechanisms, microstructure and performance in this class of ceramics. Small angle neutron scattering was used to measure the specific surface area of pores in samples aged 30 days produced with 5 different MgO powders, and to follow the evolution of pore size distribution during the setting reaction, in a time-resolved experiment. Quantification of amorphous and crystalline fraction up to 28 days was accomplished in synchronous with flexural strength tests. Results indicate that mechanical properties improve thanks to the progressive buildup of a pervasive network of tabular crystals filling the entire volume. Increasing the sintering temperature above 1500 °C yields a more compact ceramic, with less, but larger, pores, containing more crystalline fraction and less amorphous. This is consistent with the recently proposed mechanisms describing the ceramic setting reaction. The analysis of the fractured surface suggests that strength might be effectively improved modifying the density and orientation of crystals in the ceramic volume, a way for engineering new tailor-made ceramics.